Role of plasma PlGF, PDGF-AA, ANG-1, ANG-2, and the ANG-1/ANG-2 ratio as predictors of preeclampsia in a cohort of pregnant women - Machado, J. S.R. (2019)
Introduction: Preeclampsia affects 3–5% of pregnancies worldwide and is the primary cause of maternal-fetal and neonatal mortality. Previous studies show that alterations in maternal concentrations of angiogenic factors, such as PlGF, PDGF AA, ANG-1, and ANG-2, may play fundamental roles in the pathophysiology of the disease. Objective: Determine whether the PlGF, PDGF AA, ANG-1, and ANG-2 are predictors of preeclampsia occurrence in a prenatal cohort study. Patients and methods: This is a case-control study associated with a prospective cohort of pregnant women, with gestational ages between 20 and 25 weeks, composed of 30 pregnant women with preeclampsia (PE) and 90 healthy pregnant women (HP). The plasma concentrations of the markers were determined using the ELISA method. The comparison between the case and control groups was performed using the t test on the SAS® 9.4 software. Also, ROC curves were constructed to evaluate the predictive potential of the biomarkers. Results: Differences in the concentrations of PlGF, PDGF AA, ANG-1 and ANG-2, and the ANG-1/ANG-2 ratio were not observed between the PE and the HP groups. The predictive capacity of the biomarkers was assessed using ROC curves, in which the area under the curve for PlGF AUC = 0.55; PDGF AA AUC = 0.55; ANG-1 AUC = 0.47; ANG-2 AUC = 0.51, and the ANG-1/ANG-2 ratio AUC = 0.57. Conclusion: In pregnant women, with gestational ages between 20 and 25 weeks significant differences in biomarker concentrations between groups PE and HP were not observed. The ROC curves showed that the biomarkers were ineffective as preeclampsia predictors in the analyzed cohort.